Non-capsular based immunization approaches to prevent Streptococcus pneumoniae infection - Silva, Pedro H.; Vázquez, Yaneisi; Campusano, Camilo; Retamal-Díaz, Angello; Lay, Margarita K.; Muñoz, Christian A.; González, Pablo A.; Kalergis, Alexis M.; Bueno, Susan M. (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus pneumoniae is a Gram-positive bacterium and the leading cause of bacterial pneumonia in children and the elderly worldwide. Currently, two types of licensed vaccines are available to prevent the disease caused by this pathogen: the 23-valent pneumococcal polysaccharide-based vaccine and the 7-, 10, 13, 15 and 20-valent pneumococcal conjugate vaccine. However, these vaccines, composed of the principal capsular polysaccharide of leading serotypes of this bacterium, have some problems, such as high production costs and serotype-dependent effectiveness. These drawbacks have stimulated research initiatives into non-capsular-based vaccines in search of a universal vaccine against S. pneumoniae. In the last decades, several research groups have been developing various new vaccines against this bacterium based on recombinant proteins, live attenuated bacterium, inactivated whole-cell vaccines, and other newer platforms. Here, we review and discuss the status of non-capsular vaccines against S. pneumoniae and the future of these alternatives in a post-pandemic scenario.